1992
DOI: 10.1093/ajcp/97.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Hairy Leukoplakia by Exfoliative Cytologic Methods

Abstract: The cytologic characteristics of hairy leukoplakia (HL) are described based on the findings observed in four lesions. All cases were confirmed by histologic study, and Epstein-Barr virus DNA was detected by means of in situ hybridization of tissue sections. All smears from the lesions exhibited a distinctive appearance and three types of epithelial changes were observed: (1) intranuclear inclusions of Cowdry type A, (2) intranuclear inclusions with a ground-glass appearance, and (3) clumping and margination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
5

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
0
13
0
5
Order By: Relevance
“…In 1992, Fraga-Fernandez 11 concluded that the conventional cytopathology, based on nuclear features, might prove to be a useful, simple, low cost, and reliable method to diagnose OHL. Migliorati et al 22 (1993) and Dias et al 6 (1998) reported similar results 11,22 . Subclinical OHL was first described in 1995 by Mabruk et al 20 (1995).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In 1992, Fraga-Fernandez 11 concluded that the conventional cytopathology, based on nuclear features, might prove to be a useful, simple, low cost, and reliable method to diagnose OHL. Migliorati et al 22 (1993) and Dias et al 6 (1998) reported similar results 11,22 . Subclinical OHL was first described in 1995 by Mabruk et al 20 (1995).…”
Section: Introductionmentioning
confidence: 71%
“…OHL diagnosis is now based on cell morphology (histopathology and cytopathology), associated or not with EBV demonstration (immunohistochemistry, in situ hybridization, polymerase chain reaction or electronic microscopy). Many studies have demonstrated cytopathology specificity 6,7,11 . In HIV children, the accomplishment of a biopsy represents difficulty comparable to that involved in its accomplishment in adults, amplified by the delicate approach involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those techniques are very complex and expensive. The nuclear changes that represent EBV cytopathic effects can be visualized by histopathology and cytopathology (Fraga-Fernández et al 1990, Fraga-Fernández & Vicandi-Plaza 1992, Migliorati et al 1993, Dias et al 1999, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Besides molecular methods to detect the presence of EBV in OHL suspect lesions, the diagnosis might be done through the identification of nuclear alterations that represent the cytopathic effect of EBV on keratinocytes: Cowdry A inclusion, ground glass and nuclear beading. Although these alterations are observed in both histopathological and cytopathological exams, the later one has been considered the best method to diagnose clinical and subclinical OHL (Fraga-Fernández & Vicandi-Plaza 1992, Migliorati et al 1993, Dias et al 2000. There is only one disease associated with EBV replicative infection in immunocompetent patients: infectious mononucleosis.…”
mentioning
confidence: 99%